"Bosom vipers": Endemic versus epidemic disease. (27th July 2020) - Pelling, Margaret
Abstract: Epidemic diseases are defined by excess. They are dramatic and they attract attention. Endemic diseases, on the other hand, are regarded as "normal" and tend to be neglected. Yet it is clear that this contrast can entail inaccurate impressions of risk, as well as disparities in the imperative to action. This paper looks at two examples, one from the early modern period and the other from the 19th century. The earliest attempts in England to define excess mortality, primarily from plague, came in the form of parish registration, which led, in London, to the publication of Bills of Mortality. The first to analyse the Bills in order to define risk was the London tradesman John Graunt. The causes of death recorded in the Bills were a reflection of popular opinion, but Graunt used the process of aggregation to reveal mistaken ideas about the most notorious diseases, some of which were endemic rather than epidemic. He also regarded "chronical" diseases as the best measure of the healthiness of a city. In the 19th century, the centrality of plague was replaced by that of cholera, which has attracted much attention from social historians. Yet the case for public health reform was founded not on the random and comparatively isolated epidemics of cholera, but on the constant mortality caused by what were called the continued fevers, notably typhus and typhoid. The Benthamite sanitarians adopted an increasingly simplified, localist approach, which was at odds with professional opinion but was adjusted to the need both to increase popular understanding and to promote official action where it was most likely to be effective. When cholera receded, major endemic causes of death remained in the form of respiratory disease and infant mortality. Uncertainties and problems of identification and comparability persisted into the 20th century and beyond.